The polymorphic pseudokinase ROP5 controls virulence in Toxoplasma gondii by regulating the active kinase ROP18. - Michael S Behnke; Sarah J Fentress; Mona Mashayekhi; Lucy X Li; Gregory A Taylor; L David Sibley (PLoS Pathogens)
Secretory polymorphic serine/threonine kinases control pathogenesis of Toxoplasma gondii in the mouse. Genetic studies show that the pseudokinase ROP5 is essential for acute virulence, but do not reveal its mechanism of action. Here we demonstrate that ROP5 controls virulence by blocking IFN-γ mediated clearance in activated macrophages. ROP5 was required for the catalytic activity of the active S/T kinase ROP18, which phosphorylates host immunity related GTPases (IRGs) and protects the parasite from clearance. ROP5 directly regulated activity of ROP18 in vitro, and both proteins were necessary to avoid IRG recruitment and clearance in macrophages. Clearance of both the Δrop5 and Δrop18 mutants was reversed in macrophages lacking Irgm3, which is required for IRG function, and the virulence defect was fully restored in Irgm3(-/-) mice. Our findings establish that the pseudokinase ROP5 controls the activity of ROP18, thereby blocking IRG mediated clearance in macrophages. Additionally, ROP5 has other functions that are also Irgm3 and IFN-γ dependent, indicting it plays a general role in governing virulence factors that block immunity.